PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SDN 112 PEKANBARU - Tuti Deriani Deriani; Putri Yuanita Yuanita; Titi Solfitri Solfitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Based of this research is the student‘s learning result in mathematics grade III SDN 112 Pekanbaru under the Mastery Minimum Criteria. This research aims to improve the learning process and improve learning result in mathermatics by applying the model of cooperative student Team Achievement Division (STAD). Subjects in this research were student of class 111 SDN 112 Pekanbaru that were 37 students consisting 22 boys and 15 girls. This reseatch is a class action research by two cycles. Each cycle has four phases, they were planning, implementation, observation and reflection. Research instrument which consists of learning tools, which are Syllabus, Learning Implementation Plans, and Student Worksheer. The data analysis technique utilized comsist of descriptive data analysis technique which is divided into qualitative and quantitative data analysis technique. The result from this research shows the activity of the teacher and student had performend well after has been made. An increase in the number of students who received grades of 20 and 30 as many as 26 students on first cycle and 28 students on second cycle. That is also an increase in the number of students who achieve a score of KKM on the base. The development of the results of this research indicate that the application of the cooperative Student Teams Achievement Division (STAD) can improve the learning process and improve studen’s learning resuits in the class III SDN 112 Pekanbaru on the academic year 2014/2015. Keywords: mathematics learning Result,learning Process, Cooperative learning student Teams Achievement Division (STAD),Classroom Action Research